Directions for 21st Century Lifelong Learning Institutes: Elucidating Questions from Osher Lifelong Learning Institute Studies - Talmage, Craig Allen; Hansen, Robert Jack; Knopf, Richard C.; Thaxton, Steven P. (Alberta Journal of Educational Research, 2018)
The literature regarding lifelong learning is robust, while the literature on lifelong learning institutions, centers, and programs remain under-researched in comparison. This article draws insights from a specific network of lifelong learning institutes with a rich history and high rapport in the United States: the Osher Lifelong Learning Institute (OLLI) network. Sixty articles regarding OLLIs are catalogued and highlighted to elucidate twelve thematic areas and twelve questions for future research and practice. In particular, these themes are related to adult education, healthy aging, and educational gerontology. The article concludes by reflecting on trends in and needs for institutional research and practice. Les publications portant sur l’éducation permanente sont nombreuses, contrairement à celles touchant les institutions, centres et programmes d’éducation permanente qui, en comparaison, demeurent généralement mal connus. Cet article recueille des idées d’un réseau d’instituts d’éducation permanente ayant un passé riche et de bons rapports aux États-Unis : le réseau Osher Lifelong Learning Institute (OLLI). Soixante articles portant sur OLLI ont été catalogués et analysés pour faire ressortir douze thèmes et douze questions pour la recherche et la pratique à l’avenir. Ces thèmes se rattachent à l’éducation des adultes, le vieillissement sain et la gérontologie éducative. L’article se termine par des réflexions sur des tendances et des besoins relatifs à la recherche et la pratique institutionnelles. Mots clés : recherche institutionnelle, éducation permanente, ainés, éducation des adultes, universités adaptées aux personnes âgées